Effect of Turmeric Powder Supplementation on Physical and Chemical Egg Quality, Antioxidant Activity, and Yolk Fatty Acid Profile - Muhammad Fathin Hanif; Ali Agus; Bambang Ariyadi; Muhlisin -; Sesotya Raka Pambuka (Veterinary Integrative Sciences)
Turmeric powder (TP) supplementation is a widely used strategy to enhance hens' productivity and potentially mitigate egg fat oxidation by increasing antioxidant activity. Therefore, this study aimed to investigate the impact of TP supplementation on egg quality, antioxidant activity, and yolk fatty acid profile. A total of 100 56-week-old Novogen strain laying hens, matched in body weight (1799 ± 124 g), were divided into four treatments (with 5 replications per treatment, and 5 hens per replication). The treatments included control (CON), basal diet + 0.25% TP (T25), basal diet + 0.5% TP (T50), and basal diet + 0.75% TP (T75) administered for 8 weeks. Egg samples were collected on days 28 and 56 for analysis of physical and chemical quality, antioxidant activity, and fatty acid profile. On day 28, TP supplementation at 0.25% increased egg weight and specific gravity (P <0.05), while on day 56, the supplementation at 0.50% and 0.75% reduced yolk cholesterol content (P <0.05). TP supplementation at 0.5% and 0.75% also increased antioxidant activity and decreased malondialdehyde (MDA) content (P <0.05). In conclusion, supplemention of TP enhanced egg quality, and antioxidant activity and also decreased cholesterol.